Is Organizational Ambidexterity a Good Booster to Supply Chain Flexibility in the Textile and Apparel Industry? - Seimon, A. T. M.; Endagamage, D. M. (Future Science / FSH-PH Publications, 2022)
The manner by which a firm’s supply chain adapts to environment dynamics demands greater attention because the frequency and speed of change vary from industry-to-industry, business-to-business. Building on the relationship between manufacturing strategy and the environment, the purpose of this paper is to analyze the direct impact of environmental dynamism on supply chain flexibility, and the indirect impact of achieving supply chain flexibility the environment requires through organizational ambidexterity in the Sri Lankan textile and apparel industry, an industry under increased pressure to be more flexible and the highest export revenue contributor to the economy. A positivism paradigm provided the foundation for this explanatory research. A cross-sectional survey method was used to collect data from operations or supply chain managers across firms in the Sri Lankan textile and apparel industry. Eighty-seven responses were received and analyzed using the SmartPLS software. As a preliminary result, this study finds that there is a significant positive impact of environmental dynamism on supply chain flexibility and this relationship is partially mediated by organizational ambidexterity. Moreover, the results reveal a significant positive impact among the variables; environmental dynamism, organizational ambidexterity, and supply chain flexibility. In the practical context, managers need to be aware of environmental changes to identify areas that require investment in flexibility as it incurs both costs and risks for a firm. Practicing organizational ambidexterity helps managers to refine existing processes to maintain competitive advantage, and achieve the optimal degree of flexibility required by the firm and its environment.